Transforming the Dynamics of Climate Politics in Japan: Business’ Response to Securitization - Takahiro Yamada (Politics and Governance, 2021)
In 2020, Japan suddenly changed course and made carbon neutrality its intermediate target. In an attempt to understand this drastic policy change, this article analyzes the effects of climate security discourses on the perception of the Japanese business community, which holds the pivotal position in Japan’s climate policy. It particularly focuses on the effect of securitization on the source–impact asymmetry, one of the intrinsic features identified as a major obstacle to effective climate governance. From this standpoint, the article measures the extent to which the issue of climate change has been securitized in Japan, and also the extent to which the Japanese business community has come to share the securitizers’ sense of exigency. In so doing, this article employs the text-mining method called KH Coder to analyze relevant government documents as well as statements issued by Keidanren (also known as Japan Business Federation). The analysis shows that the Ministry of the Environment together with other governmental actors has collectively securitized the issue within the context of Japanese society, but that its impact on industry has been indirect, pointing to the complexity of its causal impact.